Development of Anti-Ageing Cream from Chicken Feathers - Siti Nur Khairunisa, Mohd Amir; Gupta, Arun; Syed Mohd Saufi, Tuan Chik; Kausar, Ahmad (2014)
This work presents the development of anti-ageing cream. Keratin protein derived from chicken feathers is used as an active ingredient in creams. Keratin was extracted by using reducing agent. Anti-ageing creams were produced by using several ingredients comprise of emulsifier, emollient, preservatives and surfactant. The creams were formulated using safe ingredients that include competitively price materials which are easily available in Malaysia. All the formulations were evaluated for acute skin irritancy involving animal study. Our observations on rabbit skin indicated that these formulations did not produce any skin irritation and enhance the skin structure. For stability study, all creams formulated had shown no changes in pH, colour and phase separation. Using keratin as an active ingredient in biomedical products will not only provide benefits to consumers – it will also encourage responsible waste management and sustainable commercial activities.